5.1.64 Problems 6301 to 6400

Table 5.127: First order ode

#

ODE

Mathematica

Maple

14372

\[ {}y^{\prime } = \frac {1}{\sqrt {15-x^{2}-y^{2}}} \]

14373

\[ {}y^{\prime } = \frac {3 y}{\left (x -5\right ) \left (x +3\right )}+{\mathrm e}^{-x} \]

14374

\[ {}y^{\prime } = \frac {x y}{x^{2}+y^{2}} \]

14375

\[ {}y^{\prime } = \frac {1}{x y} \]

14376

\[ {}y^{\prime } = \ln \left (y-1\right ) \]

14377

\[ {}y^{\prime } = \sqrt {\left (y+2\right ) \left (y-1\right )} \]

14378

\[ {}y^{\prime } = \frac {y}{y-x} \]

14379

\[ {}y^{\prime } = \frac {x}{y^{2}} \]

14380

\[ {}y^{\prime } = \frac {\sqrt {y}}{x} \]

14381

\[ {}y^{\prime } = \frac {x y}{1-y} \]

14382

\[ {}y^{\prime } = \left (x y\right )^{{1}/{3}} \]

14383

\[ {}y^{\prime } = \sqrt {\frac {y-4}{x}} \]

14384

\[ {}y^{\prime } = -\frac {y}{x}+y^{{1}/{4}} \]

14385

\[ {}y^{\prime } = 4 y-5 \]

14386

\[ {}y^{\prime }+3 y = 1 \]

14387

\[ {}y^{\prime } = a y+b \]

14388

\[ {}y^{\prime } = x^{2}+{\mathrm e}^{x}-\sin \left (x \right ) \]

14389

\[ {}y^{\prime } = x y+\frac {1}{x^{2}+1} \]

14390

\[ {}y^{\prime } = \frac {y}{x}+\cos \left (x \right ) \]

14391

\[ {}y^{\prime } = \frac {y}{x}+\tan \left (x \right ) \]

14392

\[ {}y^{\prime } = \frac {y}{-x^{2}+4}+\sqrt {x} \]

14393

\[ {}y^{\prime } = \frac {y}{-x^{2}+4}+\sqrt {x} \]

14394

\[ {}y^{\prime } = y \cot \left (x \right )+\csc \left (x \right ) \]

14395

\[ {}y^{\prime } = -x \sqrt {1-y^{2}} \]

14396

\[ {}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2} \]

14397

\[ {}y^{\prime } = 1+3 x \]

14398

\[ {}y^{\prime } = x +\frac {1}{x} \]

14399

\[ {}y^{\prime } = 2 \sin \left (x \right ) \]

14400

\[ {}y^{\prime } = x \sin \left (x \right ) \]

14401

\[ {}y^{\prime } = \frac {1}{x -1} \]

14402

\[ {}y^{\prime } = \frac {1}{x -1} \]

14403

\[ {}y^{\prime } = \frac {1}{x^{2}-1} \]

14404

\[ {}y^{\prime } = \frac {1}{x^{2}-1} \]

14405

\[ {}y^{\prime } = \tan \left (x \right ) \]

14406

\[ {}y^{\prime } = \tan \left (x \right ) \]

14407

\[ {}y^{\prime } = 3 y \]

14408

\[ {}y^{\prime } = 1-y \]

14409

\[ {}y^{\prime } = 1-y \]

14410

\[ {}y^{\prime } = x \,{\mathrm e}^{y-x^{2}} \]

14411

\[ {}y^{\prime } = \frac {y}{x} \]

14412

\[ {}y^{\prime } = \frac {2 x}{y} \]

14413

\[ {}y^{\prime } = -2 y+y^{2} \]

14414

\[ {}y^{\prime } = x y+x \]

14415

\[ {}x \,{\mathrm e}^{y}+y^{\prime } = 0 \]

14416

\[ {}y-x^{2} y^{\prime } = 0 \]

14417

\[ {}2 y y^{\prime } = 1 \]

14418

\[ {}2 x y y^{\prime }+y^{2} = -1 \]

14419

\[ {}y^{\prime } = \frac {1-x y}{x^{2}} \]

14420

\[ {}y^{\prime } = -\frac {y \left (y+2 x \right )}{x \left (x +2 y\right )} \]

14421

\[ {}y^{\prime } = \frac {y^{2}}{1-x y} \]

14422

\[ {}y^{\prime } = 1+4 y \]

14423

\[ {}y^{\prime } = x y+2 \]

14424

\[ {}y^{\prime } = \frac {y}{x} \]

14425

\[ {}y^{\prime } = \frac {y}{x -1}+x^{2} \]

14426

\[ {}y^{\prime } = \frac {y}{x}+\sin \left (x^{2}\right ) \]

14427

\[ {}y^{\prime } = \frac {2 y}{x}+{\mathrm e}^{x} \]

14428

\[ {}y^{\prime } = y \cot \left (x \right )+\sin \left (x \right ) \]

14429

\[ {}x -y y^{\prime } = 0 \]

14430

\[ {}-x y^{\prime }+y = 0 \]

14431

\[ {}x^{2}-y+x y^{\prime } = 0 \]

14432

\[ {}x y \left (1-y\right )-2 y^{\prime } = 0 \]

14433

\[ {}x \left (1-y^{3}\right )-3 y^{\prime } y^{2} = 0 \]

14434

\[ {}\left (2 x -1\right ) y+x \left (1+x \right ) y^{\prime } = 0 \]

14435

\[ {}y^{\prime } = \frac {1}{x -1} \]

14436

\[ {}y^{\prime } = x +y \]

14437

\[ {}y^{\prime } = \frac {y}{x} \]

14438

\[ {}y^{\prime } = \frac {y}{x} \]

14439

\[ {}y^{\prime } = \frac {y}{-x^{2}+1}+\sqrt {x} \]

14440

\[ {}y^{\prime } = \frac {y}{-x^{2}+1}+\sqrt {x} \]

14441

\[ {}y^{\prime } = \frac {y}{-x^{2}+1}+\sqrt {x} \]

14442

\[ {}y^{\prime } = y^{2} \]

14443

\[ {}y^{\prime } = y^{2} \]

14444

\[ {}y^{\prime } = y^{2} \]

14445

\[ {}y^{\prime } = y^{3} \]

14446

\[ {}y^{\prime } = y^{3} \]

14447

\[ {}y^{\prime } = y^{3} \]

14448

\[ {}y^{\prime } = -\frac {3 x^{2}}{2 y} \]

14449

\[ {}y^{\prime } = -\frac {3 x^{2}}{2 y} \]

14450

\[ {}y^{\prime } = -\frac {3 x^{2}}{2 y} \]

14451

\[ {}y^{\prime } = -\frac {3 x^{2}}{2 y} \]

14452

\[ {}y^{\prime } = \frac {\sqrt {y}}{x} \]

14453

\[ {}y^{\prime } = \frac {\sqrt {y}}{x} \]

14454

\[ {}y^{\prime } = \frac {\sqrt {y}}{x} \]

14455

\[ {}y^{\prime } = \frac {\sqrt {y}}{x} \]

14456

\[ {}y^{\prime } = 3 x y^{{1}/{3}} \]

14457

\[ {}y^{\prime } = 3 x y^{{1}/{3}} \]

14458

\[ {}y^{\prime } = 3 x y^{{1}/{3}} \]

14459

\[ {}y^{\prime } = 3 x y^{{1}/{3}} \]

14460

\[ {}y^{\prime } = 3 x y^{{1}/{3}} \]

14461

\[ {}y^{\prime } = \sqrt {\left (y+2\right ) \left (y-1\right )} \]

14462

\[ {}y^{\prime } = \sqrt {\left (y+2\right ) \left (y-1\right )} \]

14463

\[ {}y^{\prime } = \sqrt {\left (y+2\right ) \left (y-1\right )} \]

14464

\[ {}y^{\prime } = \frac {y}{y-x} \]

14465

\[ {}y^{\prime } = \frac {y}{y-x} \]

14466

\[ {}y^{\prime } = \frac {y}{y-x} \]

14467

\[ {}y^{\prime } = \frac {y}{y-x} \]

14468

\[ {}y^{\prime } = \frac {x y}{x^{2}+y^{2}} \]

14469

\[ {}y^{\prime } = \frac {x y}{x^{2}+y^{2}} \]

14470

\[ {}y^{\prime } = \frac {x y}{x^{2}+y^{2}} \]

14471

\[ {}y^{\prime } = x \sqrt {1-y^{2}} \]